SELF IMPRESSION IN POEMS WRITTEN BY ROBERT FROST: A PHENOMENOLOGICAL PSYCHOLOGICAL PERSPECTIVE - LAKSANA, NURDIN KRIDHA (2011)
This research paper's aim is at exposing the characteristics of fully functioning person of phenomenological psychology in Robert Frost's poems. The objective of the study is to analyze the structural elements of the poems and analyze the poems based on the fully functioning person in phenomenological psychology perspective. In doing so, the writer uses Carl Rogers's theory to answer the problem of the study. The study uses qualitative research. The technique of data collection is library research. The primary data are poems of Robert Frost and the secondary data are books, article, author's biography, and so forth, which relate to the subject matters. Robert Frost's poems deal much with struggle for the better life and also with the characteristics of fully functioning person in phenomenological psychology, namely openness to experience, existential living, organismic trusting, experiential freedom, and creativity. All of the speakers in Robert Frost's poems have a good self-concept and his or her self-concept is automatically developed as long as the speaker can respond to all of his experience in positive way.